REDESAIN KAWASAN MAKAM SULTAN SURIANSYAH - Zaki, Ahmad; Heldiansyah, J.C (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The graveyard of Sultan Suriansyah is the graveyard of the first Banjar King who converted to Islam and helped raise Islam in the South Kalimantan. This graveyard is one of the religious tours that is crowded with people from various regions. However, not many people know the history this place has. Therefore, there was a plan to redesign the graveyard area of the Sultan Suriansyah which would preserve history and become an educational area for those who visit here. To realize the redesign of the graveyard area of the Sultan Suriansyah, a disprogramming method is used, with the application of the concept of dimensional space in the zoning that divides the area and provides space to maintain and show the history of the place to the people who visit the area.